Modulation of sphingosine 1‐phosphate by hepatobiliary cholesterol handling. Issue 11 (12th September 2020) - Kurano, Makoto; Tsukamoto, Kazuhisa; Hara, Masumi; Tsuneyama, Koichi; Nishikawa, Takako; Ikeda, Hitoshi; Yatomi, Yutaka
Abstract: Hepatobiliary cholesterol handling, mediated by Niemann‐Pick C1‐like 1 protein (NPC1L1) and ABCG5/8, is well‐known to contribute to the homeostasis of cholesterol. We attempted to elucidate the impact of hepatobiliary cholesterol handling on the homeostasis of sphingolipids and lysophospholipids, especially sphingosine 1‐phosphate (S1P). We induced the overexpression of NPC1L1 or ABCG5/8 in the mouse liver. Hepatic NPC1L1 overexpression increased the plasma and hepatic S1P levels, while it decreased the biliary S1P levels, and all of these changes were inhibited by ezetimibe. The ability of HDL to activate Akt in the endothelial cells was augmented by hepatic NPC1L1 overexpression. NPC1L1‐mediated S1P transport was confirmed by both in vitro and in vivo studies conducted using C17 S1P, an exogenous S1P analog. Upregulation of apolipoprotein M (apoM) was involved in these modulations, although apoM was not necessary for these modulations. Moreover, the increase in the plasma S1P levels also observed in ABCG5/8‐overexpressing mice was dependent on the elevation of the plasma apoM levels. In regard to other sphingolipids and lysophospholipids, ceramides were similarly modulated by NPC1L1 to S1P, while other lipids were differently influenced by NPC1L1 or ABCG5/8 from S1P. Hepatobiliary cholesterol handling might also regulate the functional lipids, such as S1P.